Correlation between the Need for Cognitive Closure and Narrative Creativity in Secondary Education - Ortega-Martín, José Luis (Int J Environ Res Public Health, 2021)
(1) Background: The present study analyzed the need for cognitive closure and narrative creativity in adolescents. The aim was to demonstrate a strong relationship between narrative creativity and the need for cognitive closure. We analyzed a group of participants by applying a lie scale integrated with the Need for Closure Scale to detect potential relationships between students that entered the lie scale group (discarded) and those that were not discarded by exploring the following variables: gender, school type, group condition, and narrative creativity. (2) Methods: The instruments used were the Need for Closure Scale and the Test of Creative Imagination for Young People, PIC-J. Students of English as a foreign language in the 3rd year of secondary education from two schools were selected based on their availability to participate in the project. The students were aged 14 to 16 with a non-probabilistic sampling value of N = 117. (3) Results: Results show a negative correlation between narrative creativity and the need for cognitive closure. The need for cognitive closure is mainly manifested in two of its five dimensions: order and predictability. In addition, the group analysis of the lie scale revealed a higher tendency of male students to be less likely to respond truthfully. Meanwhile, the percentage of participants in the lie scale group was higher in rural schools. (4) Conclusions: In conclusion, students who do not belong to the lie scale group seem to have more creativity than students in the lie scale group, while students in the lie scale group have a lower final course grade than students in the non lie scale group.